The Impact of Outpatient Prenatal Care Visitor Restrictions on Pregnant Patients and Partners During the COVID-19 Pandemic - Christina Collart; Caitlin Craighead; Susannah Rose; Richard Frankel; Brownsyne Tucker Edmonds; Uma Perni; Edward K. Chien; Marissa Coleridge; Angela Ranzini; Ruth M. Farrell (Mary Ann Liebert, 2022)
Introduction: During the early months of the COVID-19 pandemic, several health care facilities enacted visitor restrictions to help reduce the spread of SARS-CoV-2 among patients, front-line workers in health care systems, and communities. The impact and burden of policy updates on visitor restrictions put forth by the COVID-19 pandemic can be seen on patients and families, most often in the acute care setting and skilled nursing facilities. Yet, the effects of visitor restrictions in the prenatal care setting were unknown. We conducted a study to investigate the impact of these policies on pregnant patients who received outpatient prenatal care. Methods: We conducted a qualitative study to explore pregnant patients' experiences with prenatal health care delivery between May and July 2020. In-depth interviews were conducted with pregnant patients in the first and second trimester of pregnancy, who received their prenatal care at the onset of the pandemic in the United States. Results: Participants noted increased maternal concern, anxiety, and mental health concerns stemming from the lack of in-person partner support. They noted disappointment and lost experiences for the patient during pregnancy, seeking support from her partner during pregnancy, experiences felt to be critical for postpartum health and wellbeing. There was also concern about the negative impact of restrictions on prenatal care quality and experience. Conclusions: This study demonstrates the impact of visitor restrictions on patients' prenatal care experience and perception of health care quality during the COVID-19 pandemic. Future public health strategies should be individualized to different patient populations addressing knowledge, health literacy, and socioeconomic status, and developed in conjunction with pregnant patients as key stakeholders in the delivery of prenatal health care.